Comodulation of Dengue and Chikungunya Virus Infection During a Coinfection Scenario in Human Cell Lines - Taraphdar, Debjani; Singh, Bharati; Pattanayak, Sabyasachi; Kiran, Avula; Kokavalla, Poornima; Alam, Mohd. Faraz; Syed, Gulam Hussain (Frontiers in Cellular and Infection Microbiology, 2022)
Dengue virus (DENV) and Chikungunya virus (CHIKV) are the arboviruses that pose a threat to global public health. Co-infection and antibody-dependent enhancement (ADE) are major areas of concern during DENV and CHIKV infection, which can alter the clinical severity. Acute hepatic illness is common manifestation and major sign of disease severity upon infection with either Dengue or Chikungunya. Hence, in this study we characterized the co-existence and interaction between both the viruses in human hepatic (Huh7) cells during co-infection/super-infection scenario. We observed that prior presence or subsequent super-infection with DENV, enhanced CHIKV replication. However, prior CHIKV infection negatively affected DENV. In comparison to mono-infection, co-infections with both DENV and CHIKV resulted in lower infectivity as compared to mono-infections with modest suppression of CHIKV but dramatic suppression of DENV replication. Subsequent investigations revealed that sub-neutralizing levels of DENV or CHIKV anti-sera can respectively promote ADE of CHIKV or DENV infection in FcγRII bearing human myelogenous leukemia cell line K562. Our observations suggest that CHIKV has a fitness advantage over DENV in hepatic cells and prior DENV infection may enhance CHIKV disease severity if the patient subsequently contracts CHIKV. This study highlights the natural possibility of Dengue-Chikungunya co-infection and their subsequent modulation in human hepatic cells. These observations have important implications in regions where both viruses are prevalent and calls for proper management of DENV-CHIKV co-infected patients